APPLICATION OF RAPID RESOLUTION LIQUID CHROMATOGRAPHY TO THE ANALYSIS OF SOME PESTICIDE RESIDUES IN APPLE JUICE - VELKOSKA-MARKOVSKA, Lenche; PETANOVSKA-ILIEVSKA, Biljana; MARKOVSKI, Aleksandar (Journal Agriculture and Forestry, 2017)
This paper presents the application of a new, precise, accurate and reliable rapid resolution liquid chromatography (RRLC) method with ultraviolet-diode array detection (UV-DAD) for the determination of some organonitrogen and organophosphorus pesticide residues in apple juice samples. The successful separation and quantitative determination of analytes were achieved using a Poroshell EC 120-C18 (50 mm x 3 mm; 2.7 µm) analytical column maintained at 25 0C and the detection was monitored at 220 nm and 270 nm. The mixture of acetonitrile/water (50/50, V/V) was used as a mobile phase, with flow rate of 1 mL/min. Specificity, selectivity, linearity, precision, accuracy and limit of quantification (LOQ) were examined to assess the validity of the developed method according to European Commission guidelines for pesticide residue analytical methods and all the performance characteristics were found within acceptance criteria. The obtained values for multiple correlation coefficients (R2) were > 0.96, relative standard deviation (RSD) of retention times and peak areas were ≤ 1.15 %, and recoveries ranged from 93.98 % - 118.60 %, with RSD ≤ 1.77 %. The proposed method was successfully applied for the determination of investigated pesticides in apple juice samples. The detectable residues of examined pesticides were not found in the analysed samples.